2012
DOI: 10.1021/jp3047246
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics and Efficiencies for the Hydroxyl and Sulfate Radical Based Oxidation of Artificial Sweeteners in Water

Abstract: Over the past several decades, the increased use of artificial sweeteners as dietary supplements has resulted in rising concentrations of these contaminants being detected in influent waters entering treatment facilities. As conventional treatments may not quantitatively remove these sweeteners, radical-based advanced oxidation and reduction (AO/RP) treatments could be a viable alternative. In this study, we have established the reaction kinetics for both hydroxyl ((•)OH) and sulfate (SO(4)(•-)) radical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…According to the results, the photocatalytic transformation of SAC under both irradiation sources, starts by the hydroxylation of the molecule giving rise to the formation of three isomers (TP4, TP5, TP6). The hydroxylation mechanism proposed in the present study is consistent with a previous work that reported relatively high reactivity of hydroxyl radicals towards the studied sweetener and proposed that the oxidation mechanism involves the addition of hydroxyl radicals in the aromatic ring, resulting in hydroxylated products …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…According to the results, the photocatalytic transformation of SAC under both irradiation sources, starts by the hydroxylation of the molecule giving rise to the formation of three isomers (TP4, TP5, TP6). The hydroxylation mechanism proposed in the present study is consistent with a previous work that reported relatively high reactivity of hydroxyl radicals towards the studied sweetener and proposed that the oxidation mechanism involves the addition of hydroxyl radicals in the aromatic ring, resulting in hydroxylated products …”
Section: Resultsmentioning
confidence: 72%
“…The hydroxylation mechanism proposed in the present study is consistent with a previous work that reported relatively high reactivity of hydroxyl radicals towards the studied sweetener and proposed that the oxidation mechanism involves the addition of hydroxyl radicals in the aromatic ring, resulting in hydroxylated products. 37 Hydroxylation of phenyl ring as well as N atom can be considered. Sequential hydroxylation of the above-mentioned TPs results to di-and tri-hydroxy derivatives (TP7 and TP1).…”
Section: Tps and Reaction Pathwaysmentioning
confidence: 99%
“…The rate constant of t-BuOH with hydroxyl radical (k HO•/t-BuOH = 6.0 x 10 8 M -¹ s -¹ [17]) is around three-order higher than with sulfate radical (k SO4• -/ t-BuOH = 8.4 x 10 5 M -¹ s -¹ [44]). Thus, the addition of an excessive amount of t-BuOH allowed a strong suppression of the reaction of target compounds with hydroxyl radical [45][46][47]. Though the presence of the competitors and t-BuOH influenced the steady-state radical concentrations, without the radical concentration values, the second order rate constant of BZ4 with the radical species could still be calculated according to equation (1) without knowledge of the radical concentrations [48] which is in fact an integrated equation for eq (8)- (11) in Gonzalez-Olmos, 2011 [49]:…”
Section: Photolytic Experimentsmentioning
confidence: 99%
“…j As reported by Hyunwoong (2010). k As reported by Toth et al (2012). l As reported by Dodd et al (2009).…”
mentioning
confidence: 76%